2006
DOI: 10.1203/01.pdr.0000219121.15634.d1
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Muscle Peristaltic Activity in the Fetal Rat

Abstract: Aside for the potential for tonic contraction, the airway smooth muscle exhibits intermittent phasic rhythmic activity that may contribute to lung growth during fetal life. Therefore, we examined 4th generation rat 18 -22 d gestation fetal, 4 -6 d of age newborn and adult bronchial ring from Sprague Dawley rats to compare differences in smooth muscle function. We hypothesized that phasic contractions were greatest before birth. Bronchial muscle spontaneous rhythmic contractions were greatest in the fetus and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Consequently, it has been hypothesized that the intracellular calcium concentration is abnormally elevated in asthmatic airway smooth muscle cells (Amrani and Panettieri, 1998;Amrani et al, 2004;Moynihan et al, 2008). The U46619-induced tonic contractions in rat bronchi is dependent on the extracellular calcium concentration, while it was not affected by intracellular calcium pools (Parvez et al, 2006). In the present study, calcium-free media in the presence of Ca 2+ chelator EGTA resulted in complete suppression of the U46619-induced contraction in both fresh and organ cultured bronchial segments.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Consequently, it has been hypothesized that the intracellular calcium concentration is abnormally elevated in asthmatic airway smooth muscle cells (Amrani and Panettieri, 1998;Amrani et al, 2004;Moynihan et al, 2008). The U46619-induced tonic contractions in rat bronchi is dependent on the extracellular calcium concentration, while it was not affected by intracellular calcium pools (Parvez et al, 2006). In the present study, calcium-free media in the presence of Ca 2+ chelator EGTA resulted in complete suppression of the U46619-induced contraction in both fresh and organ cultured bronchial segments.…”
Section: Discussionsupporting
confidence: 43%
“…To evaluate the role of intracellular Ca 2+ signaling in mediating the enhancement of U46619-induced contraction, the inhibitory effects of calcium-free solution in the presence of the Ca 2+ chelator EGTA (1 mM) (Parvez et al, 2006), the voltage-gated calcium channel (VGCC) blocker nifedipine (10 μM) (Skogvall et al, 2007) and the receptor-operated calcium channel (ROCC) blocker SKF96365 (10 μM) (Merritt et al, 1990) were determined in both fresh and organ cultured segments.…”
Section: Role Of Extracellular Ca 2+ Influx In Enhancement Of U46619-mentioning
confidence: 99%
“…[135][136][137][138]. The current authors later showed the importance of this mechanism in SR refilling in bovine ASM [16], as have others in murine ASM [139]. This Ca 2+ -influx pathway appears to be dependent on the availability of extracellular Na + [16].…”
Section: +mentioning
confidence: 78%
“…From the earliest stages of lung development and throughout subsequent prenatal life the developing lung is itself vigorously mechanically active [74][75][76][77]. Peristaltic waves of airway smooth muscle (ASM) rhythmically propagate throughout the airway tree with resulting propulsion of all important lung liquid (Fig.…”
Section: The Biomechanical Regulation Of Lung Developmentmentioning
confidence: 99%